Analisis Faktor-Faktor yang Mempengaruhi Audit Delay pada Perusahaan LQ 45 yang Terdaftar di Bursa Efek Indonesia - Muammar Khaddafi; Asmaul Husna; Arliansyah (Jurnal EMT KITA, 2022)
The purpose of this research is to analyze the impact of the Size of the company, firm Age, Auditor Opinion, business Income, and Auditor Quality of the Audit Delay companies listed in the Indonesia Stock Exchange partially and simultaneously. The population in this research were LQ 45 Companies listed on the Stock Exchange in the year 2010-2013 as many as 19 companies were taken by purposive sampling. The analysis method used in this study is method documentation secondary data taken through www.idx.co.id and analyzed using multiple linear regression. The results showed the Lq 45 Companies listed in Indonesia Stock Exchange in 2010-2013 that Company Size has no significant influence on Audit Delay, The Age of the company has no significant influence on the Audit Delay, Auditor Opinion has no significant influence on the Audit Delay, Business Income has no significant influence to the Audit Delay, Audit Quality has no significant influence to the Audit Delay, and Size of the company, Firm Age, Auditor Opinion, the Business Income and Auditor Quality has no significant jointly with Audit Delay.